Preparation method and application of bionic strain hardening mechanical property elastomer

CN119505126APending Publication Date: 2025-02-25JIANGNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411845506.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing flexible materials are difficult to match when reacting to the physiological state of biological bodies, especially in bending, folding, torsion, stretching and other movements, resulting in insufficient mechanical properties of the sensor parts.

Method used

ABA-type triblock copolymer was prepared by RAFT polymerization, combining hard phase and soft phase to form a coordinated dissipation network to achieve the strain hardening mechanical properties of the material.

Benefits of technology

It realizes the material's low Young's modulus and high strength mutually repulsive mechanical properties, has excellent elasticity and strong strain enhancement capabilities, and is suitable for wearable and implantable sensor parts and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505126A_ABST
    Figure CN119505126A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a bionic strain hardening mechanical property elastomer, and belongs to the technical field of functional polymer materials. According to the preparation method provided by the invention, an ABA type triblock copolymer is prepared by utilizing an RAFT (Reversible Addition-Fragmentation Chain Transfer) method, and a continuous flexible soft phase and a dispersed rigid hard phase are formed through self-assembly of a block molecular chain and micro-phase separation. A synergistic dissipation network is formed in a mode of combining a hard phase and a soft phase, the flexible soft phase endows the material with stretchability, and the hard phase with high modulus and high strength bears a load in a shearing mode, so that the strength and fracture resistance are improved. An elastic material having intrinsic strain hardening properties with a low initial modulus (141 kPa) and a high hardening capacity (a hardening multiple of 56 times) is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polymer materials, and in particular relates to a preparation method and application of a bionic strain hardening mechanical property elastomer. Background Art

[0002] With the rapid development of flexible sensing fields such as flexible wearable and implantable electronic technologies, flexible materials have become indispensable materials for key components such as sensing layers and protective layers of flexible electronic devices. They not only need to have basic sensing properties such as high sensitivity and stability, but also need to meet the requirements of synchronous movement and deformation with the sensing tissue, such as bending, folding, twisting, stretching, etc. Therefore, the mechanical compatibility of flexible sensing materials and soft biological tissues has naturally become a core issue in the design and preparation of sensing materials.

[0003] At present, most commercial flexible materials, such as polydimethylsiloxane (PDMS), thermoplastic polyurethane (TPU) and silicone rubber, have high Young's modulus or poor resilience, so flexible sensors constructed from these materials are difficult to reflect the actual physiological state of biological organisms. In synthetic materials, flexibility and strength are two mutually exclusive mechanical properties. However, the special J-type stress-strain mechanical response of biological tissues gives them the mutually exclusive mechanical properties of low Young's modulus and high strength. They are soft at small deformations (Young's modulus ~100kPa), and as the deformation increases, the muscle tissue will significantly harden and show higher strength (~1MPa). This mechanical property that rigidity increases with the increase of applied strain or stress is called reversible strain hardening. On the one hand, the strain hardening property can limit the infinite deformation of biological tissues and effectively prevent damage caused by large-scale deformation to maintain their tissue structural integrity and biological functions. On the other hand, the low modulus property at small deformations ensures its flexibility in deformation.

[0004] Therefore, by imitating the reversible strain hardening characteristics of biological tissues, the unification of two mutually exclusive mechanical properties, flexibility and strength, can be achieved in the material. While the material has high mechanical stability, it also gives it good mechanical matching with soft biological tissues, and monitors electrophysiological signals accurately and with high fidelity. Therefore, the development of soft material systems with mechanical properties that mimic biological tissues is conducive to improving the mechanical matching between bionic soft materials and biological organisms. It has unique advantages in biological tissue and organ sensing and is an ideal flexible matrix material for integrated electronic devices. It is of vital importance for applications in wearable devices, implantable devices, soft robots, artificial skin, and human-computer interaction systems. Summary of the invention

[0005] A method for preparing a bionic strain hardening mechanical property elastomer, the preparation method comprising the following steps:

[0006] Step 1, block polymerizing 2-6 styrene units and 10-20 acrylic acid units on a trithioester small molecule RAFT monomer through a bulk RAFT polymerization reaction to prepare an amphiphilic macromolecular RAFT agent, which is referred to as Macro-RAFT;

[0007] Step 2, using the Macro-RAFT obtained in step 1 as a RAFT agent, based on a reversible addition-fragmentation chain transfer polymerization method, adding a styrene monomer to carry out a first-stage reaction, then adding an acrylic ester monomer to carry out a second-stage reaction, and finally adding a styrene monomer to carry out a third-stage reaction, and polymerizing by three consecutive feedings to obtain a triblock copolymer;

[0008] Step 3, dissolving the triblock copolymer obtained in step 2 in tetrahydrofuran solvent to obtain a casting solution, then casting it on a flat silicon wafer and placing it in a drying oven at room temperature to slowly evaporate the solvent, and after the solvent evaporates, placing it in a vacuum oven for annealing to obtain an elastomer with strain hardening mechanical properties; the RAFT polymerization reaction is bulk polymerization.

[0009] This patent invents a method for preparing a biomimetic strain-hardening mechanical property elastomer, which forms a synergistic dissipative network by combining a hard phase and a soft phase. The flexible soft phase gives the material stretchability, while the hard phase with high modulus and high strength bears the load in the form of shear, thereby improving strength and fracture resistance. This patent selects acrylic monomers and styrene monomers, and prepares ABA-type triblock copolymers by RAFT method. In the solution system, due to the difference in solubility between polystyrene and polyacrylate in the solvent, the styrene block components self-assemble through non-covalent bond interactions, and drive the block polymers to aggregate and undergo microphase separation during the evaporation of the solvent, thereby forming a continuous polyacrylate flexible soft phase and a polystyrene dispersed rigid hard phase structure. Among them, the low glass transition temperature (T g ) can ensure the flexibility of the polymer. The polystyrene hard phase can act as a macro cross-linking agent to increase the cross-linking density and can also bear the stress fracture resistance transmitted by the soft phase. That is, the purpose of preparing an elastomer with intrinsic strain hardening mechanical properties is achieved. This elastomer is expected to be used in the fields of wearable and implantable sensors, soft robots, artificial skin, and human-computer interaction systems.

[0010] The small molecule RAFT agent in step 1 is 2-(dodecylsulfanyl)thioacylalkylpropionic acid;.

[0011] The acrylate monomer in step 2 is ethoxyethoxyethyl acrylate, methoxyethyl acrylate or 2-ethylhexyl acrylate.

[0012] In one embodiment, the solvent used in the RAFT polymerization reaction in step 1 is dimethylformamide, dimethyl sulfoxide or 1,4-dioxane.

[0013] In one embodiment, the RAFT polymerization reaction in step 2 is emulsion polymerization, and the solid mass fraction in the emulsion is 20-40%.

[0014] In one embodiment, the mass concentration of the casting solution in step 3 is 4-6%; the solvent volatilization time in step 3 is controlled to be 2-3 days; and the annealing temperature in step 3 is 70-90°C.

[0015] In one embodiment, step 1 is specifically: mixing 2-(dodecylsulfanyl)thioacylalkylpropionic acid, an initiator, acrylic acid and a solvent, stirring to dissolve and deoxygenate, reacting at 80° C., adding styrene and an initiator after the reaction is completed, and separating and purifying to obtain Macro-RAFT after the reaction is completed.

[0016] The amount of initiator added each time in step 1 is 1 to 5 mol% of 2-(dodecylsulfanyl)thioacylalkylpropionic acid, the molar ratio of 2-(dodecylsulfanyl)thioacylalkylpropionic acid to acrylic acid is 1:10-1:20, and the molar ratio of 2-(dodecylsulfanyl)thioacylalkylpropionic acid to styrene is 1:2-1:6.

[0017] In one embodiment, step 2 is specifically:

[0018] The Macro-RAFT reagent, deionized water, styrene, and initiator potassium persulfate were stirred and dissolved to remove oxygen, and then sealed and subjected to the first stage reaction at 70-80°C;

[0019] After the first stage reaction is completed, ethoxyethoxyethyl acrylate, initiator, and deionized water are added to carry out the second stage reaction at 40-60°C;

[0020] After the second stage reaction is completed, styrene, initiator and deionized water are added to carry out the third stage reaction at 40-60° C. The precipitate is separated and purified to obtain a triblock copolymer;

[0021] During each addition in the first, second and third stages, the solid content in the aqueous solution is ensured to be maintained at 20-40%.

[0022] The molar ratio of the Macro-RAFT agent in step 2 to the initiator in each stage is 100:1-100:5, and the mass ratio of styrene to acrylate monomer is 2:8-4:6;

[0023] In one embodiment, step 3 is specifically as follows: dissolving the triblock copolymer in tetrahydrofuran solvent with a mass concentration of 5%, adding conductive lithium salt lithium bis(trifluoromethylsulfonylimide), then casting on a flat silicon wafer and slowly evaporating the solvent at room temperature, and the above steps are all performed in a glove box; after the solvent evaporates, annealing in a vacuum oven can obtain a conductive elastomer with strain hardening mechanical properties.

[0024] The second object of the present invention is to provide a conductive elastomer with bionic strain hardening mechanical properties prepared by the above method.

[0025] The third object of the present invention is to apply the above-mentioned conductive elastomer to wearable and implantable sensor devices, soft robots, electronic skin, etc.

[0026] Beneficial effects:

[0027] The present invention proposes to use ABA-type triblock molecular chains to construct an elastomer with strain hardening mechanical properties. The J-type stress-strain mechanical response of the elastomer enables it to have mutually exclusive mechanical properties of low Young's modulus and high strength. The elastomer also has mechanical properties such as low Young's modulus (141kPa), high strength (2.91MPa), excellent elasticity and strong strain enhancement ability (stiffness enhancement 56 times).

[0028] The elastomeric material of the present invention has higher resilience performance because there is no non-covalent interaction force between the molecular chains of the middle block component PDEEA.

[0029] The elastomeric material of the present invention has a COC group on the PDEEA side chain and a Li + The ion-dipole interaction can improve the compatibility between PDEEA and conductive lithium salt. The prepared conductive composite material can maintain high conductivity on the basis of excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 a is the synthesis route of Macro-RAFT reagent, b is the NMR mass spectrum of Macro-RAFT reagent;

[0031] Figure 2 NMR mass spectrum of poly(styrene-b-ethoxyethoxyethyl acrylate-b-styrene) block copolymer;

[0032] Figure 3 a is the stress-strain curve of poly(styrene-b-ethoxyethoxyethyl acrylate-b-styrene) block copolymer, and b is the differential modulus curve of poly(styrene-b-ethoxyethoxyethyl acrylate-b-styrene) block copolymer;

[0033] Figure 4 Bionic strain hardening mechanical properties Demonstration of strain hardening mechanics of elastomers;

[0034] Figure 5 Electrical conductivity of conductive elastomers inspired by biomimetic strain hardening mechanical properties. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0036] Example 1 Preparation of biomimetic strain hardening mechanical properties elastomer

[0037] (1) Preparation of Macro-RAFT Agents:

[0038] The synthetic route of Macro-RAFT reagents is as follows Figure 1 As shown, first, 2-(dodecylsulfanyl)thioacylalkylpropionic acid (1.5 g, 4.3 mmol), initiator 4,4'-azo(4-cyanovaleric acid) (0.06 g, 0.215 mmol), acrylic acid (6.2 g, 86 mmol), 1,4-dioxane were added to a three-necked flask, stirred to dissolve and nitrogen was bubbled to deoxygenate for 2 h. The above solution was then placed in an 80°C oil bath to react for 5 h. After the above reaction was completed, styrene (2.23 g, 21.5 mmol) and 4,4'-azo(4-cyanovaleric acid) (0.06 g, 0.215 mmol) were added and reacted for 12 h. After the reaction was completed, a light yellow solution was obtained.

[0039] The product solution obtained above was poured into cyclohexane for precipitation, and the lower precipitate was washed with cyclohexane for several times, and a light yellow solid was obtained after filtration, and then dried in a vacuum oven at 30°C for 12 hours. The NMR mass spectrometry showed that Figure 1 As shown, the chemical shift peak (ppm) is assigned to: 0.87 (3H, C 11 H 22 CH3), 6.79 (25H, -Ph-H), 12.16 (21H, -COOH), proving that the Macro-RAFT agent was successfully prepared.

[0040] (2) Preparation of poly(styrene-b-ethoxyethoxyethyl acrylate-b-styrene) block copolymer:

[0041] Macro-RAFT reagent (0.805g, 0.348mmol), styrene (1.731, 16.6mmol), initiator potassium persulfate (0.0047g, 0.0174mmol), stirred and dissolved, deoxygenated for 1h, sealed and placed at 80℃ for 5h for the first stage reaction; after the first stage reaction, ethoxyethoxyethyl acrylate (13.847g, 0.0735mol), initiator azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol), deionized water was injected to continue the reaction at 50℃ for 10h for the second stage reaction; after the second stage reaction was completed, styrene (1.731, 16.6mmol), azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol), deionized water was added to continue the reaction at 50℃ for 10h. Each addition ensured that the solid content in the aqueous solution was maintained at 30%. After the reaction, the emulsion was added to a 3 wt% dilute hydrochloric acid solution to break the emulsion and collect the precipitate. The precipitate was washed to neutrality and then freeze-dried to remove water. Figure 2 As shown, the chemical shift peak (ppm) is assigned to: 0.85 (3H, C 11 H 22 CH3), 4.10 (2H, -COO-CH2), 6.63 (25H, -Ph-H), proving that the poly(styrene-b-ethoxyethoxyethyl acrylate-b-styrene) block copolymer was successfully prepared.

[0042] (3) The poly(styrene-b-ethoxyethoxyethyl acrylate-b-styrene) block copolymer was dissolved in tetrahydrofuran solvent, and after casting, it was placed in a drying oven to slowly evaporate the solvent. After the solvent evaporated, it was placed in a vacuum oven at 80° C. for annealing. The mechanical strength of the elastomer prepared in this embodiment is as follows: Figure 3 As shown in FIG. 1 , the fracture strength is 1.4 MPa and the initial modulus is 80 kPa. The elastomer prepared in this embodiment has strain hardening mechanical properties, such as Figure 4 As shown, the strain is larger under the initial light load, while the strain is smaller under the step-by-step heavy load.

[0043] Example 2 Preparation of biomimetic strain hardening mechanical properties elastomer

[0044] (1) Preparation of Macro-RAFT Agents:

[0045] The steps are the same as Example 1.

[0046] (2) Preparation of poly(styrene-b-ethoxyethoxyethyl acrylate-b-styrene) block copolymer:

[0047] Macro-RAFT reagent (0.805g, 0.348mmol), styrene (2.60g, 25mmol), initiator potassium persulfate (0.0047g, 0.0174mmol), stirred and dissolved, deoxygenated for 1h, sealed and placed at 80℃ for 5h for the first stage reaction; after the first stage reaction, ethoxyethoxyethyl acrylate (20.77g, 110mmol), initiator azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol), deionized water was injected to continue the reaction at 50℃ for 10h for the second stage reaction; after the second stage reaction was completed, styrene (2.60g, 25mmol), azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol) were added, and deionized water was continued to react at 50℃ for 10h. Each addition ensured that the solid content in the aqueous solution was maintained at 30%. After the reaction is completed, the emulsion is added into a 3 wt % dilute hydrochloric acid solution to break the emulsion and collect the precipitate. The precipitate is washed to neutrality and then freeze-dried to remove water.

[0048] The remaining steps are the same as those in Example 1. The mechanical strength of the elastomer obtained in this embodiment is as follows Figure 3 As shown, the breaking strength is 1.9 MPa and the initial modulus is 120 kPa.

[0049] Example 3 Preparation of biomimetic strain hardening mechanical properties elastomer

[0050] (1) Preparation of Macro-RAFT Agents:

[0051] The steps are the same as Example 1.

[0052] (2) Preparation of poly(styrene-b-ethoxyethoxyethyl acrylate-b-styrene) block copolymer:

[0053] Macro-RAFT reagent (0.805g, 0.348mmol), styrene (3.46g, 33mmol), initiator potassium persulfate (0.0047g, 0.0174mmol), stirred and dissolved, deoxygenated for 1h, sealed and placed at 80℃ for 5h for the first stage reaction; after the first stage reaction, ethoxyethoxyethyl acrylate (27.70g, 150mmol), initiator azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol), deionized water was injected to continue the reaction at 50℃ for 10h for the second stage reaction; after the second stage reaction was completed, styrene (3.46g, 33mmol), azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol) were added, and deionized water was continued to react at 50℃ for 10h. Each addition ensured that the solid content in the aqueous solution was maintained at 30%. After the reaction is completed, the emulsion is added into a 3 wt % dilute hydrochloric acid solution to break the emulsion and collect the precipitate. The precipitate is washed to neutrality and then freeze-dried to remove water.

[0054] The remaining steps are the same as those in Example 1. The mechanical strength of the elastomer obtained in this embodiment is as follows Figure 3 As shown, the breaking strength is 2.9 MPa and the initial modulus is 140 kPa.

[0055] Example 4 Preparation of biomimetic strain hardening mechanical properties elastomer

[0056] (1) Preparation of Macro-RAFT Agents:

[0057] The steps are the same as Example 1.

[0058] (2) Preparation of poly(styrene-b-methoxyethyl acrylate-b-styrene) block copolymer:

[0059] Macro-RAFT reagent (0.805g, 0.348mmol), styrene (2.60g, 25mmol), initiator potassium persulfate (0.0047g, 0.0174mmol), stirred and dissolved, deoxygenated for 1h, sealed and placed at 80℃ for 5h for the first stage reaction; after the first stage reaction, methoxyethyl acrylate (20.77g, 110mmol), initiator azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol), deionized water was injected at 50℃ for 10h for the second stage reaction; after the second stage reaction was completed, styrene (2.60g, 25mmol), azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol) were added, and deionized water was added at 50℃ for 10h. Each addition ensured that the solid content in the aqueous solution was maintained at 30%. After the reaction is completed, the emulsion is added into a 3 wt % dilute hydrochloric acid solution to break the emulsion and collect the precipitate. The precipitate is washed to neutrality and then freeze-dried to remove water.

[0060] The remaining steps are the same as Example 1.

[0061] Example 5 Preparation of biomimetic strain hardening mechanical properties elastomer

[0062] (1) Preparation of Macro-RAFT Agents:

[0063] The steps are the same as Example 1.

[0064] (2) Preparation of poly(styrene-b-2-ethylhexyl acrylate-b-styrene) block copolymer:

[0065] Macro-RAFT reagent (0.805g, 0.348mmol), styrene (2.60g, 25mmol), initiator potassium persulfate (0.0047g, 0.0174mmol), stirred and dissolved, deoxygenated for 1h, sealed and placed at 80℃ for 5h for the first stage reaction; after the first stage reaction, 2-ethylhexyl acrylate (20.77g, 110mmol), initiator azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol), deionized water was injected to continue the reaction at 50℃ for 10h for the second stage reaction; after the second stage reaction was completed, styrene (2.60g, 25mmol), azobisisobutylimidazoline hydrochloride (0.005g, 0.0174mmol) were added, and deionized water was continued to react at 50℃ for 10h. Each addition ensured that the solid content in the aqueous solution was maintained at 30%. After the reaction is completed, the emulsion is added into a 3 wt % dilute hydrochloric acid solution to break the emulsion and collect the precipitate. The precipitate is washed to neutrality and then freeze-dried to remove water.

[0066] The remaining steps are the same as Example 1.

[0067] Example 6 Preparation of Conductive Elastomer with Bionic Strain Hardening Mechanical Properties

[0068] 2g of PS-PDEEA-PS polymer prepared in Example 2 was dissolved in tetrahydrofuran solvent, 12.5wt% of conductive lithium salt lithium bis(trifluoromethylsulfonyl)imide was added, and then cast on a flat silicon wafer and the solvent was slowly evaporated at room temperature for 5 days. The above steps were all completed in a glove box. After the solvent evaporated, it was placed in a vacuum oven at 80°C for annealing to obtain a conductive elastomer with strain hardening mechanical properties. The conductive elastomer prepared in this example has a conductivity as shown in FIG. Figure 5 As shown, the conductivity is 1.4×10 5 S / cm.

[0069] Example 7 Preparation of Conductive Elastomer with Bionic Strain Hardening Mechanical Properties

[0070] 2g of PS-PDEEA-PS polymer prepared in Example 2 was dissolved in tetrahydrofuran solvent, 25wt% of conductive lithium salt lithium bis(trifluoromethylsulfonyl)imide was added, and then cast on a flat silicon wafer and the solvent was slowly evaporated at room temperature for 5 days. The above steps were all completed in a glove box. After the solvent evaporated, it was placed in a vacuum oven at 80°C for annealing to obtain a conductive elastomer with strain hardening mechanical properties. The conductive elastomer prepared in this example has a conductivity as shown in FIG. Figure 5 As shown, the conductivity is 1.8×10 5 S / cm.

[0071] Example 8 Preparation of Conductive Elastomer with Bionic Strain Hardening Mechanical Properties

[0072] 2g of PS-PDEEA-PS polymer prepared in Example 2 was dissolved in tetrahydrofuran solvent, 50wt% of conductive lithium salt lithium bis(trifluoromethylsulfonyl)imide was added, and then cast on a flat silicon wafer and the solvent was slowly evaporated at room temperature for 5 days. The above steps were all completed in a glove box. After the solvent evaporated, it was placed in a vacuum oven at 80°C for annealing to obtain a conductive elastomer with strain hardening mechanical properties. The conductive elastomer prepared in this example has a conductivity as shown in FIG. Figure 5 As shown, the conductivity is 2.4×10 5 S / cm.

[0073] Example 9 Preparation of Conductive Elastomer with Bionic Strain Hardening Mechanical Properties

[0074] 2g of PS-PDEEA-PS polymer prepared in Example 2 was dissolved in tetrahydrofuran solvent, 100wt% of conductive lithium salt lithium bis(trifluoromethylsulfonyl)imide was added, and then cast on a flat silicon wafer and the solvent was slowly evaporated at room temperature for 5 days. The above steps were all completed in a glove box. After the solvent evaporated, it was placed in a vacuum oven at 80°C for annealing to obtain a conductive elastomer with strain hardening mechanical properties. The conductive elastomer prepared in this example has a conductivity as shown in FIG. Figure 5 As shown, the conductivity is 9.8×10 5 S / cm.

Claims

1. A method for preparing a bionic strain hardening elastomer, characterized in that: The preparation method comprises the following steps: Step 1, block polymerizing 2-6 styrene units and 10-20 acrylic acid units on a trithioester small molecule RAFT monomer through a RAFT bulk polymerization reaction to prepare an amphiphilic macromolecular RAFT agent, which is referred to as Macro-RAFT; Step 2, using the Macro-RAFT obtained in step 1 as a RAFT agent, based on a reversible addition-fragmentation chain transfer polymerization method, adding a styrene monomer to carry out a first-stage reaction, then adding an acrylic ester monomer to carry out a second-stage reaction, and finally adding a styrene monomer to carry out a third-stage reaction, and polymerizing by three consecutive feedings to obtain a triblock copolymer; Step 3, dissolving the triblock copolymer obtained in step 2 in tetrahydrofuran solvent to obtain a casting solution, then casting the solution on a flat silicon wafer and placing the solution in a drying oven at room temperature to slowly evaporate the solvent, and then placing the solution in a vacuum oven for annealing after the solvent evaporates to obtain an elastomer with strain hardening mechanical properties; The small molecule RAFT agent in step 1 is 2-(dodecylsulfanyl)thioacylalkylpropionic acid; The acrylate monomer in step 2 is ethoxyethoxyethyl acrylate, methoxyethyl acrylate or 2-ethylhexyl acrylate.

2. The method for preparing a bionic strain hardening mechanical property elastomer according to claim 1, characterized in that: The solvent used in the RAFT polymerization reaction in step 1 is dimethylformamide, dimethyl sulfoxide or 1,4-dioxane.

3. The method for preparing a bionic strain hardening mechanical property elastomer according to claim 1, characterized in that: The RAFT polymerization reaction in step 2 is emulsion polymerization, and the solid mass fraction in the emulsion is 20-40%.

4. The method for preparing a bionic strain hardening mechanical property elastomer according to claim 1, characterized in that: The mass concentration of the casting solution in step 3 is 4-6%; The solvent volatilization time in step 3 is controlled to be 3-5 days; The annealing temperature in step 3 is 70-90°C.

5. The method for preparing a bionic strain hardening mechanical property elastomer according to claim 1, characterized in that: The step 1 specifically comprises: mixing 2-(dodecylsulfanyl)thioacylalkylpropionic acid, an initiator, acrylic acid and a solvent, stirring to dissolve and deoxygenate, reacting at 70-80° C., adding styrene and an initiator after the reaction is completed, and separating and purifying to obtain Macro-RAFT.

6. The method for preparing a bionic strain hardening mechanical property elastomer according to claim 1, characterized in that: In the step 1, the amount of the initiator added each time is 1 to 5 mol% of 2-(dodecylsulfanyl)thioacylalkylpropionic acid, the molar ratio of 2-(dodecylsulfanyl)thioacylalkylpropionic acid to acrylic acid is 1:10-1:20, and the molar ratio of 2-(dodecylsulfanyl)thioacylalkylpropionic acid to styrene is 1:2-1:

6.

7. The method for preparing a bionic strain hardening mechanical property elastomer according to claim 1, characterized in that: Step 2 is as follows: The Macro-RAFT reagent, deionized water, styrene, and initiator potassium persulfate were stirred and dissolved to remove oxygen, and then sealed and subjected to the first stage reaction at 70-80°C; After the first stage reaction is completed, acrylate monomer, initiator, and deionized water are added to carry out the second stage reaction at 40-60°C; After the second stage reaction is completed, styrene, initiator and deionized water are added to carry out the third stage reaction at 40-60° C. The precipitate is separated and purified to obtain a triblock copolymer; During each addition in the first, second and third stages, the solid content in the aqueous solution is ensured to be maintained at 20-40%.

8. The method for preparing a bionic strain hardening mechanical property elastomer according to claim 1 or 7, characterized in that: The molar ratio of the Macro-RAFT agent in step 2 to the initiator in each stage is 100:1-100:5, and the mass ratio of styrene to acrylate monomer is 2:8-4:

6.

9. An elastomer having strain hardening mechanical properties obtained by the method according to any one of claims 1 to 8.

10. An elastomer having strain hardening mechanical properties obtained by the method of claims 1-9 for use in the fields of sensing, tissue engineering and soft robotics engineering.